The five year school medical--time for change. Issue 2 (February 1990) - Smith, G C; Powell, A; Reynolds, K; Campbell, C A
Abstract : School medical records of 1000 children born in 1981 were studied retrospectively. They showed that once known medical problems and those screened for by the school nurse (hearing, vision, growth) were excluded, only 17 problems requiring treatment were discovered: speech (n = 10), development (n = 3), undescended testes (n = 3), and phimosis (n = 1). This indicates that routine screening by a nurse, backed up by selective medical examination by the school doctor, is efficient and effective.